Bibliometric Analysis of Ferroptosis in Stroke From 2013 to 2021 - Chen, Yuhua; Long, Tianlin; Xu, Quanhua; Zhang, Chi (Frontiers in Pharmacology, 2022)
Background: Stroke is a major cause of long-term disability and death, but the clinical therapeutic strategy for stroke is limited and more research must be conducted to explore the possible avenues for stroke treatment and recovery. Since ferroptosis is defined, its role in the body has become the focus of attention and discussion, including in stroke. Methods: In this work, we aim to systematically discuss the “ferroptosis in stroke” research by bibliometric analysis. Documents were retrieved from the Web of Science Core Collection database on October 30, 2021. Statistical analysis and visualization analysis were conducted by the VOSviewer 1.6.15. Results: Ninety-nine documents were identified for bibliometric analysis. Research on “ferroptosis in stroke” has been rapidly developing and has remained the focus of many scholars and organizations in the last few years, but the Chinese groups in this field still lacked collaboration with others. Documents and citation analysis suggested that Rajiv R. Ratan and Brent R. Stockwell are active researchers, and the research by Qingzhang Tuo, Ishraq Alim, and Qian Li are more important drivers in the development of the field. Keywords associated with lipid peroxidation, ferroptosis, iron, oxidative stress, and cell death had high frequency, but apoptosis, necroptosis, pyroptosis, and autophagy had scant research, and there may be more research ideas in the future by scholars. Conclusion: Further exploration of the mechanisms of crosstalk between ferroptosis and other programmed cell death may improve clinical applications and therapeutic effects against stroke. Scholars will also continue to pay attention to and be interested in the hot topic “ferroptosis in stroke”, to produce more exciting results and provide new insights into the bottleneck of stroke treatment.